Causes and effects of school abuse on children's physical, psychological, and social well-being, as well as their academic performance - Ameer Salah-Aldeen Abdulrazaq; Zaman Ahmed Hrefish; Hussein Ali Abdulabbas (Genius Journals, 2022)
All forms of violence against those under the age of eighteen, whether perpetrated by parents, peers, caregivers, teachers, strangers or partners, are considered a social problem affecting public health and human rights. One in three children between the ages of two and seventeen has been a victim of violence, and this is a worrying statistic. Few studies have found evidence of physical violence in schools in relation to school violence. However, this can lead to long-term physical, mental, and emotional issues, as well as permanent physical effects and disabilities. Children who are subjected to any form of school violence are more likely to be inactive, have a reactive attachment disorder, be obese or overweight, smoke, drink, or use drugs, and are more likely to develop diseases of the cardiovascular system, lungs, or other organ systems, as well as report self-reported health problems. Positive, nonviolent discipline has been shown in international studies to produce better results, while exposure to any form of violence is linked to an increase in the number and severity of other forms of violence.
Keywords: School Abuse; Causes; Effects; children's physical